Comprehensive Evaluation of Transit-Oriented Development (TOD) Guidance Systems: A Case Study of Shanghai TODs - Zhan Zhang; Bochen Cao; Alima Adalaiti; Linjun Lu; Xinyi Fang (Advances in Civil Engineering)
Transit-oriented development (TOD) is a leading urban planning paradigm whose success largely depends on the effectiveness of its guidance systems. Although guidance systems have been extensively researched in various contexts, there is a significant gap in evaluating these systems within TOD scenarios, particularly regarding quantitative assessment methods. This study introduces a novel quantitative evaluation methodology to assess the various dimensions of guidance systems in TOD contexts. It identifies four primary criteria: normativity, effectiveness, continuity, and individualization, alongside 13 specific secondary evaluation indicators. The contributions of these indicators are determined through expert scoring using the analytic hierarchy process (AHP) and are subsequently validated through on-site user assessments. Data collection for TOD guidance systems involved scoring using a system usability scale (SUS) questionnaire and objective data measurements across five routes within two representative TODs in Shanghai. The results reveal a strong linear regression relationship between AHP quantitative scores and SUS questionnaire scores, validating the effectiveness of the proposed indicator framework. In summary, this study addresses the gap in evaluating TOD guidance systems and provides a comprehensive evaluation system to guide future design and development efforts in TOD scenarios.